Respuesta :
Q1. The answer is 19.
f(x)=2x+8
g(x)=5
(f + g)(x) = f(x) + g(x)
(f + g)(3) = f(3) + g(x)
f(3) = 2 * 3 + 8 = 6 + 8 = 14
g(3) = 5
(f + g)(3) = f(3) + g(x) = 14 + 5 = 19
Q2. The answer is -22.
f(x)= -2x+8
g(x)=5x
(f o g)(x) = f(g(x))
(f o g)(3) = f(g(3))
g(3) = 5 * 3 = 15
(f o g)(3) = f(g(3)) = f(15) = -2 * 15 + 8 = -30 + 8 = -22
f(x)=2x+8
g(x)=5
(f + g)(x) = f(x) + g(x)
(f + g)(3) = f(3) + g(x)
f(3) = 2 * 3 + 8 = 6 + 8 = 14
g(3) = 5
(f + g)(3) = f(3) + g(x) = 14 + 5 = 19
Q2. The answer is -22.
f(x)= -2x+8
g(x)=5x
(f o g)(x) = f(g(x))
(f o g)(3) = f(g(3))
g(3) = 5 * 3 = 15
(f o g)(3) = f(g(3)) = f(15) = -2 * 15 + 8 = -30 + 8 = -22